REKONSTRUKSI HUKUM MELALUI VICTIM TRUST FUND SEBAGAI PEMENUHAN HAK ANAK KORBAN KEKERASAN SEKSUAL - Adella Darmawan (2023)
This study aims to find out the fact of granting restitution to child victims of sexual violence which has been deemed to have failed due to many obstacles. So it is necessary to have a new mechanism that can replace the role of restitution as compensation, namely by implementing the Victim Trust Fund. This study uses a normative juridical research type, with a statute approach, conceptual approach, and a comparative approach. Where the data used comes from secondary data consisting of primary legal materials in the form of legislation, secondary legal materials in the form of library studies, and tertiary legal materials in the form of dictionaries related to law. The data analysis technique used is qualitative with the results of research that are analytical descriptive in nature. The results of this study indicate that restitution has failed to carry out its duties as compensation for child victims of sexual violence. This is caused by various factors that encourage legal critics to think that there is a need for a new mechanism that can replace the restitution function, namely the Victim Trust Fund. In order to be able to adopt this mechanism into the Indonesian legal system, it is necessary to have a legal reconstruction by adding the Victim Trust Fund clause and its mechanism to the applicable laws and regulations in Indonesia.